Phosphatidic Acid Increases Notch Signalling by Affecting Sanpodo Trafficking During Drosophila Sensory Organ Development - Vega-Macaya, F (Nature Research, 2020)
Organ cell diversity depends on binary cell-fate decisions mediated by the Notch signalling pathway during development and tissue homeostasis. A clear example is the series of binary cell-fate decisions that take place during asymmetric cell divisions that give rise to the sensory organs of Drosophila melanogaster. The regulated trafficking of Sanpodo, a transmembrane protein that potentiates receptor activity, plays a pivotal role in this process. Membrane lipids can regulate many signalling pathways by affecting receptor and ligand trafficking. It remains unknown, however, whether phosphatidic acid regulates Notch-mediated binary cell-fate decisions during asymmetric cell divisions, and what are the cellular mechanisms involved. Here we show that increased phosphatidic acid derived from Phospholipase D leads to defects in binary cell-fate decisions that are compatible with ectopic Notch activation in precursor cells, where it is normally inactive. Null mutants of numb or the α-subunit of Adaptor Protein complex-2 enhance dominantly this phenotype while removing a copy of Notch or sanpodo suppresses it. In vivo analyses show that Sanpodo localization decreases at acidic compartments, associated with increased internalization of Notch. We propose that Phospholipase D-derived phosphatidic acid promotes ectopic Notch signalling by increasing receptor endocytosis and inhibiting Sanpodo trafficking towards acidic endosomes. © 2020, The Author(s).